2014
DOI: 10.1152/ajpregu.00319.2013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and postweaning high-fat diets disturb hippocampal gene expression, learning, and memory function

Abstract: We tested the hypothesis that excess saturated fat consumption during pregnancy, lactation, and/or postweaning alters the expression of genes mediating hippocampal synaptic efficacy and impairs spatial learning and memory in adulthood. Dams were fed control chow or a diet high in saturated fat before mating, during pregnancy, and into lactation. Offspring were weaned to either standard chow or a diet high in saturated fat. The Morris Water Maze was used to evaluate spatial learning and memory. Open field testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 61 publications
7
81
1
2
Order By: Relevance
“…Finally, while the specific contributions of prenatal versus early postnatal exposure to HF diet has not been well established, results from our own cross-fostering experiments suggest that exposure at either time is sufficient to induce impairment in both Novel Object Recognition and the Barnes Maze among adult offspring [138], which, in rats, is consistent with the trajectory of hippocampal development that spans both the prenatal and early postnatal periods [139141]. Regarding potential mechanisms underlying these changes, maternal HF diet consumption has been found to increase hippocampal inflammation [126], increase plasma leptin [127], and decrease hippocampal BDNF [134,135], while alterations in placental transport of nutrients and hormones may also be involved [125]. In our own lab, we have found that maternal HF diet exposure results in offspring with decreased hippocampal gene expression of insulin receptor ( Insr ), leptin receptor ( Lepr ), and glucose transporter 1 ( Slc2a1 ) at weaning.…”
Section: Developmental Programming By Maternal Dietmentioning
confidence: 72%
See 1 more Smart Citation
“…Finally, while the specific contributions of prenatal versus early postnatal exposure to HF diet has not been well established, results from our own cross-fostering experiments suggest that exposure at either time is sufficient to induce impairment in both Novel Object Recognition and the Barnes Maze among adult offspring [138], which, in rats, is consistent with the trajectory of hippocampal development that spans both the prenatal and early postnatal periods [139141]. Regarding potential mechanisms underlying these changes, maternal HF diet consumption has been found to increase hippocampal inflammation [126], increase plasma leptin [127], and decrease hippocampal BDNF [134,135], while alterations in placental transport of nutrients and hormones may also be involved [125]. In our own lab, we have found that maternal HF diet exposure results in offspring with decreased hippocampal gene expression of insulin receptor ( Insr ), leptin receptor ( Lepr ), and glucose transporter 1 ( Slc2a1 ) at weaning.…”
Section: Developmental Programming By Maternal Dietmentioning
confidence: 72%
“…Prior work in our lab using a rat model has found that maternal exposure to a 60% HF diet increases the offspring’s risk of developing diet-induced obesity [130], while also altering leptin sensitivity [131], and ingestive behavior [132,133]. Further, several behavioral studies in mice and rats have found that maternal consumption of various HF diets can result in impairment in the Morris Water Maze [126,134] and Barnes Maze [135]. Two other studies in rats found Morris Water Maze impairment among offspring born to HF fed dams that were then continued on a HF diet after weaning [136,137].…”
Section: Developmental Programming By Maternal Dietmentioning
confidence: 99%
“…The female rats received the HFD shortly after weaning, mimicking a potential harmful maternal dietary habit, known to impact embryogenesis and fetal development [1][2][3][4][5][6], aspects which were not examined in this study. Our aim was to specifically investigate a potential cumulative detrimental effect of maternal HFD on offspring exposed to asphyxia.…”
Section: Doi: 101159/000491383mentioning
confidence: 99%
“…One of the most vulnerable brain areas affected by HFD is the hippocampus, resulting in a delayed utero development [5], learning and memory impairment, and addiction-like behaviors [6]. The mechanisms involved are exacerbated proliferation of astrocytes, increased stress response to acute stimuli [7], and altered development of the placental vasculature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to early maltreatment has been reported to induce long-lasting changes in the methylation of the Bdnf gene in the prefrontal cortex in mice (Roth et al 2009). Furthermore, Page et al (2014) demonstrated that maternal fat-rich diet significantly decreases the levels of BDNF mRNA. Therefore, there is no reason to exclude the possibility that maternal HFD feeding may program the HPA system and BDNF expression and ultimately alter adult offspring susceptibility to ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%